Post-marketing safety profile of ganirelix in women: a 20-year pharmacovigilance analysis of global adverse drug event databases (2004–2024) - Yang Yang; Zhiwei Cui; Xiaoshan Feng; Fan Zou; Xiaoling Wu (BMC Pharmacology and Toxicology)
Abstract Background Ganirelix, a third-generation GnRH antagonist, is widely used in assisted reproductive technology (ART) for rapid pituitary suppression to prevent premature luteinizing hormone (LH) surges. Despite its extensive clinical use, real-world evidence on its safety in large populations remains scarce. This study aimed to evaluate the safety profile of ganirelix by comprehensively analyzing adverse drug events (ADEs) using real-world data from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) and the Japan Adverse Drug Event Reporting (JADER) database. Methods We extracted ADE data from FAERS (Q1 2004–Q2 2024) and JADER (Q1 2009–Q1 2024). Disproportionality analyses, including reporting odds ratios (ROR), proportional reporting ratios (PRR), Bayesian Confidence Propagation Neural Networks (BCPNN), and Multi-item Gamma Poisson Shrinkage (MGPS), were employed to identify significant associations between ganirelix and ADEs. Results In the FAERS database, we identified 1,096 ganirelix-related ADE reports, spanning 26 system organ classes (SOCs). A total of 65 positive signals were detected, including ADEs consistent with drug label such as ovarian hyperstimulation syndrome (OHSS) (n = 290, ROR 2462.76, PRR 2168.48, EBGM05 1655.59, IC025 9.18), injection site pain (n = 54, ROR 3.99, PRR 3.93, EBGM05 3.13, IC025 0.31), and fetal death (n = 6, ROR 21.05, PRR 21.00, EBGM05 10.72, IC025 2.72). Additionally, unexpected signals not listed in the drug label were identified, including ectopic pregnancy (n = 7, ROR 33.02, PRR 32.93, EBGM05 17.64, IC025 3.37), maternal exposure before pregnancy (n = 30, ROR 76.09, PRR 75.16, EBGM05 74.72, IC025 6.22), dermatitis allergic (n = 4, ROR 7.98, PRR 7.97, EBGM05 3.50, IC025 1.33), and bladder tamponade (n = 4, ROR 771.47, PRR 770.3, EBGM05 311.57, IC025 7.80). The median time to ADE onset was 13 days. External validation using the JADER database (62 ganirelix-related ADE reports) confirmed four signals, including abortion (n = 19), OHSS (n = 17), missed abortion (n = 9), and fetal death (n = 8), aligning with FAERS findings. Conclusion This study provides a robust real-world safety evaluation of ganirelix, with findings corroborated by two independent pharmacovigilance databases. While consistent with clinical observations, the identification of unexpected signals warrants further pharmacoepidemiological investigations to confirm these results.